Preparation and thermal characterization of nanographene- enhanced fatty acid-based solid-liquid organic phase change material composites for thermal energy storage - Kittusamy, Ragul Kumar (Strojniški vestnik, 2022)
In this research work, nano-phase change material (NPCM) composites were prepared by adding 1 %, 2 %, and 3 % mass fractions of highly conductive carbon-based graphene nanoparticles into the base phase change material (PCM). The existence and uniform graphene dispersion in the PCM was confirmed through Raman spectrometer and scanning electron microscope (SEM) analysis. The Fourier transform infrared (FTIR) and x-Ray diffraction (XRD) results showed that all three NPCM composites were chemically stable, and their crystallinity was similar to the base PCM. For the sample with 3 % graphene, the solid-state thermal conductivity was increased by 219.89 %, and liquid-state thermal conductivity was increased by 161.65 %, with a 3.52 % drop in latent heat capacity was revealed from differential scanning calorimetry (DSC) analysis. All NPCM composites have onset and peak melting temperatures closer to the base PCM. Hence, the NPCM composites can be employed for thermal energy storage (TES) integrated solar water heater (SWH) applications.
Keywords: graphene nanoparticles; kompozit NPCM; nanodelci grafena; nano-phase change material composite; PCM materiali; phase change material; shranjevanje toplote; solar water heater; solarni grelnik vode; sončna energija; thermal energy storage